PV array reconfiguration method under partial shading conditions - Parlak, Koray Sener (Elsevier Sci Ltd, 2014)
This paper proposes a new reconfiguration method for photovoltaic arrays under partial shading conditions. With the application the method, the array can produce higher power by reconfigured connections of array. In the proposed method, each row of an array is formed by connecting the panels with close short circuit current levels as possible. A novel algorithm entitled configuration scanning algorithm is used to determine the all possible connection structures. This algorithm utilizes only short circuit current values measured at particular parts of the array. The proposed method has been tested in Matlab-Simulink environment under partial shading conditions. Results of the simulation show that the efficiency of the array is considerably increased with the presented reconfiguration method. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Photovoltaic arrays; PV array reconfiguration; Partial shaded conditions; Maximum power point